Role of the Gut Microbiome in the Pathogenesis of Crohn’s Disease - Demir, Ahmet; Kara, Sevda; Khamraev, Javlonbek (Journal of Biomedical and Techno Nanomaterials, 2025)
Crohn's disease is one of the inflammatory bowel diseases (IBD) whose pathogenesis is still not fully understood. Many studies have shown a link between dysbiosis of the gut microbiome and the development of the disease. However, the specific mechanism linking the microbiota to inflammation in Crohn's disease is still open to further exploration. This study aims to investigate the role of the gut microbiome in the pathogenesis of Crohn's disease, specifically in differentiating the composition of the microbiota in patients with active disease and in remission. This study used a cross-sectional design with a sample of 100 patients diagnosed with Crohn's disease. Fecal samples were collected and analyzed using metagenomic techniques (16S rRNA sequencing) to identify the composition of the microbiota. Analysis of inflammatory biomarkers such as C-reactive protein (CRP) is also performed to assess disease status. The results showed that patients with active disease had a decrease in the number of anti-inflammatory bacteria such as Faecalibacterium prausnitzii and an increase in pathogenic bacteria such as Escherichia coli. In addition, there was a correlation between microbiome dysbiosis and increased CRP levels in patients with active disease. Microbiome dysbiosis has an important role in exacerbating the symptoms of Crohn's disease. This study provides evidence that the management of the gut microbiota can be a new therapeutic approach in the treatment of Crohn's disease.